Examining the impact of early life adversity on adolescent sleep health: Findings from the ABCD study - Ethan T. Hunt; Keith Brazendale; Augusto César Ferreira De Moraes; Marcus Vinicius Nascimento-Ferreira; Christopher D. Pfledderer; Sarah Sampaio Izabel; Erin E. Dooley; Baojiang Chen; Alejandra Fernandez; Micah E. Johnson; Hugh Garavan; Alexandra S. Potter; et al. (Child Protection and Practice)
Background: Sleep irregularity are associated with health outcomes, particularly during adolescence. Early adversity may exacerbate sleep irregularity, but longitudinal evidence remains limited. Objective: To investigate the relationship between early adversity, social jetlag, and weekly sleep loss in youth from the Adolescent Brain Cognitive Development (ABCD) Study. Participants and setting: The sample included 11,002 adolescents (mean age at 2-year follow-up = 12.03 years, SD = 0.67) from the ABCD Study (53 % boys and 47 % girls). Racial/ethnic composition was 53 % White, 14 % Black, 20 % Hispanic, and 13 % other/multi-racial. Methods: Social jetlag and weekly sleep loss were assessed using the Munich Chronotype Questionnaire at 2-year and 3-year follow-ups. Concurrently, lifetime adversity was measured using 16 of 17 items from the Pediatric Early Adversity and Related Life Events Screener (PEARLS). Mixed-effects linear and logistic regression models examined associations between lifetime adversities and sleep, adjusting for key covariates. Results: Adolescents experienced an average of 2.13 ( ± 1.9) hours of weekly sleep loss, and 33.32 % reported four or more PEARLS. Adolescents with four or more PEARLS experienced greater weekly sleep loss (coef. = 0.38, 95 % CI: 0.26, 0.51), translating to 23 min of additional sleep loss per week. Adolescents with four or more PEARLS were also more likely to experience more than 1 h of social jetlag (aOR = 2.79, 95 % CI: 2.19, 3.55). Conclusions: Early adversity is associated with social jetlag and sleep loss in adolescence, suggesting that targeted prevention approaches may improve sleep regularity and quantity.